Сравнение эксплуатационных характеристик многофазных регулируемых асинхронных двигателей - Петрушин, В.С.; Беликова, Л.Я.; Плоткин, Ю.Р.; Еноктаев, Р.Н. (Електротехніка і електромеханіка, 2016)
Обоснована возможность создания модификаций многофазных асинхронных двигателей на базе серийных трехфазных. Рассмотрен ряд силовых схем регулируемых электроприводов, в которых обеспечивается многофазное питание
асинхронных двигателей. Анализируется работа приводов на определенную по величине и характеру нагрузку и заданным диапазоном регулирования. В результате математического моделирования определено, что температуры перегревов обмоток статоров рассматриваемых двигателей не превышают допустимых значений соответственно классу нагревостойкости изоляции. Выполнено сравнение технико-экономических показателей рассматриваемых схем и
двигателей, дающее возможность осуществить приемлемый выбор варианта. Установлены закономерности изменения фазных токов многофазных двигателей в диапазоне регулирования. Исследовано изменение виброакустических
показателей в статических и динамических режимах. Определено снижение этих показателей в двигателях с числом
фаз, превышающим три Обґрунтовано можливість створення модифікацій багатофазних асинхронних двигунів на базі серійних. Розглянуто
ряд силових схем регульованих електроприводів, в яких забезпечується багатофазне живлення асинхронних двигунів.
Аналізується робота приводів на визначене за величиною і характером навантаження і заданим діапазоном регулювання. В результаті математичного моделювання визначено, що температури прогріву обмоток статорів розглянутих двигунів не перевищують допустимих значень відповідно до класу ізоляції. Виконано порівняння технікоекономічних показників розглянутих схем і двигунів, що дає можливість здійснити прийнятний вибір варіанта.
Встановлено закономірності зміни фазних струмів багатофазних двигунів в діапазоні регулювання. Досліджено зміну
віброакустичних показників у статичних та динамічних режимах. Визначено зниження цих показників в двигунах з
числом фаз, що перевищує три Purpose. Development of mathematical models of adjustable
electrical drives with high-phase order induction motors for their
merits analysis at static and dynamical modes. Methodology. At
the mathematical modeling main kinds of physical processes taking place in the high-phase order induction motors are considered: electromagnetic, electromechanical, energetic, thermal,
mechanical, vibroacoustic ones. Besides, functional as well as
mass, frame and value indicators of frequency converters are
taking into account which permits to consider technical and economical aspects of the adjustable induction electrical drives.
Creation of high-phase order induction motors’ modifications in
possible on the base of a stock 3-phase motors of basic design.
Polyphase supply of induction motors is guaranteed by a number
of the adjustable electrical drives’ power circuits. Results. Modelling of a number of adjustable electrical drives with induction
motors of different phase number working on the same load by its
character, value and required adjustment range is carried out. At
the utilization of the family of characteristics including mechanical ones at different adjustment parameters on which loading
mechanism’s characteristics are superimposed regulation curves
representing dependences of electrical, energetic, thermal, mechanical, vibroacoustic quantities on the motors’ number of revolutions are obtained. Originality. The proposed complex models
of adjustable electrical drives with high-phase order induction
motors give a possibility to carry out the grounded choice of the
drive’s acceptable variant. Besides, they can be used as design
models at the development of adjustable high-phase order induction motors. Practical value. The investigated change of vibroacoustic indicators at static and dynamical modes has been
determined decrease of these indicators in the drives with number
of phase exceeding 3.